The immunological impact of revaccination in a hybrid-immune world - Bausch-Jurken, Mary; Alter, Galit (Frontiers in Immunology, 2025)
The global immune landscape of SARS-CoV-2 has progressively shifted from a naïve population several years ago to a population that possesses immunity to the virus through infection, vaccination, or a combination of both, known as hybrid immunity. Hybrid immunity offers a prolonged period of transmission-blocking activity, likely related to enhanced tissue-resident immunity, but also has been shown to be linked to broader humoral and cellular immune responses. Compared with vaccination or infection alone, the collective data have demonstrated that hybrid immunity offers enhanced protection against disease. Yet, despite the benefits of hybrid immunity, perpetual evolution of variants and the natural waning of immunity in vulnerable populations provides a strong rationale for revaccination. This article reviews the benefits of revaccination, including updating variant-specific immunity, bolstering humoral and cellular immune frequencies in those with hybrid immunity, and overcoming immune imprinting and enhancing effector mechanisms to raise surveillance and defense against the virus. As SARS-CoV-2 continues to evolve, updated booster vaccinations remain essential to enhance and sustain protection from disease by ensuring that the immune system is equipped to respond to contemporary strains, thereby reducing the impact of future outbreaks and mitigating the burden of COVID-19, especially among vulnerable populations.